Selected short stories - Tagore, Rabindranath, 1861-1941 (Tagore, Rabindranath, 2000)
This collection of the short stories of Nobel Laureate Rabindranath Tagore, translated into English from Bengali, is the first title in a major project undertaken by OUP in collaboration with Visva-Bharati to publish the English translations of a wide range of Tagore's writings including poetry, non-fiction prose, and fiction.